2009
DOI: 10.1016/j.cub.2008.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Evolution: How Fruit Flies Adapt to Seasonal Stresses

Abstract: Fruit flies inhabit a wide range of latitudes, requiring adaptation to the varying local climates. A recent study reports evidence that the ability of North American flies to endure the winter involves adaptive polymorphism of the couch potato gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…This general gene response is the background on which evolutionary changes may be operating during evolution (Waddington 1961). In fact, some environmental stress‐detecting genes that have been modelled by evolution (Williams & Sokolowski 2009) like have also been detected in our analysis.…”
Section: Discussionsupporting
confidence: 56%
“…This general gene response is the background on which evolutionary changes may be operating during evolution (Waddington 1961). In fact, some environmental stress‐detecting genes that have been modelled by evolution (Williams & Sokolowski 2009) like have also been detected in our analysis.…”
Section: Discussionsupporting
confidence: 56%
“…However, some evidence for local adaptation to abiotic environments has been found in D . melanogaster populations, for example in terms of a correlation between local climate and ability to enter diapause [ 53 ] or between altitude and desiccation resistance [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and photoperiod are environmental factors providing signals that regulate the induction of stress responses (Teets & Denlinger, ; Tyukmaeva, Salminen, Kankare, Knott, & Hoikkala, ; Williams & Sokolowski, ). For example, hardening or acclimation responses induced by thermal variation can modulate resistance to temperature extremes as well as impact upon starvation and desiccation resistance (Alemu, Alemneh, Pertoldi, Ambelu, & Bahrndorff, ; Parkash, Aggarwal, Singh, Lambhod, & Ranga, ; Schou, Loeschcke, & Kristensen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the importance of photoperiod was not observed in a nearby highland population generally experiencing lower temperatures. The species‐ and population‐specific effects of photoperiod suggest that responses have a genetic basis and/or can be affected by assay conditions (Williams & Sokolowski, ). Apart from the effects of photoperiod on thermal resistance, Fischer et al () showed that photoperiod is important for a range of life‐history traits including growth rate, development time, and body size in Protophormia terraenovae and for many of the traits investigated results showed interactions between temperature and photoperiod.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation